Pregunta
upstudy study bank question image url

Solve the equation by factoring. \( 8 x^{2}+10 x-7=0 \) Rewrite the equation in factored form. \( \square=0 \) (Factor completely.) The solution set is \( \{\square\} \) (Use a comma to separate answers as needed. Type each solution only once.)

Ask by Bolton Parry. in the United States
Feb 02,2025

Solución de tutoría real

Respuesta verificada por el tutor

Responder

\( (2x - 1)(4x + 7) = 0 \), solutions: \( x = -\frac{7}{4}, \frac{1}{2} \)

Solución

To solve the quadratic equation \( 8x^{2} + 10x - 7 = 0 \) by factoring, follow these steps: ### Step 1: Factor the Equation 1. **Identify coefficients**: - \( a = 8 \) - \( b = 10 \) - \( c = -7 \) 2. **Find two numbers that multiply to \( a \times c = 8 \times (-7) = -56 \) and add up to \( b = 10 \)**: - The numbers are **14** and **-4** because: - \( 14 \times (-4) = -56 \) - \( 14 + (-4) = 10 \) 3. **Rewrite the middle term using these numbers**: \[ 8x^{2} + 14x - 4x - 7 = 0 \] 4. **Factor by grouping**: \[ (8x^{2} + 14x) + (-4x - 7) = 0 \\ 2x(4x + 7) - 1(4x + 7) = 0 \] 5. **Factor out the common binomial**: \[ (2x - 1)(4x + 7) = 0 \] So, the **factored form** of the equation is: \[ (2x - 1)(4x + 7) = 0 \] ### Step 2: Find the Solution Set Set each factor equal to zero and solve for \( x \): 1. \( 2x - 1 = 0 \) \[ 2x = 1 \\ x = \frac{1}{2} \] 2. \( 4x + 7 = 0 \) \[ 4x = -7 \\ x = -\frac{7}{4} \] Therefore, the **solution set** is: \[ \left\{ -\frac{7}{4}, \frac{1}{2} \right\} \] ### Final Answer - **Factored Form**: \[ (2x - 1)(4x + 7) = 0 \] - **Solution Set**: \[ \left\{ -\frac{7}{4}, \frac{1}{2} \right\} \]

Revisado y aprobado por el equipo de tutoría de UpStudy

error msg
Explicar
Simplifique esta solución

Mind Expander

To solve the equation \( 8x^2 + 10x - 7 = 0 \) by factoring, we first look for two numbers that multiply to \( 8 \times -7 = -56 \) and add to \( 10 \). Those numbers are \( 14 \) and \( -4 \). We can then rewrite the equation as: \( 8x^2 + 14x - 4x - 7 = 0 \) Now, grouping the terms results in: \( 2x(4x + 7) - 1(4x + 7) = 0 \) This gives us: \( (2x - 1)(4x + 7) = 0 \) Setting each factor equal to zero: 1. \( 2x - 1 = 0 \) leads to \( x = \frac{1}{2} \) 2. \( 4x + 7 = 0 \) leads to \( x = -\frac{7}{4} \) Now we can write the complete factored form and the solution set: \((2x - 1)(4x + 7) = 0\) The solution set is \(\{\frac{1}{2}, -\frac{7}{4}\}\).

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad